Pencegahan Perceraian Karena Kekerasan dalam Rumah Tangga Perspektif Ekologi Bronfenbrenner - Firah Amalia Nurbeta; Eko Hidayat; Ahmad Fauzan (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aimed to analyze the prevention of divorce caused by domestic violence through Bronfenbrenner’s ecological perspective. The study was motivated by the increasing divorce rate in Indonesia, in which domestic violence became one of the major causes. Domestic violence not only affected the physical condition of victims but also influenced the psychological, social, and economic conditions of the family. This study employed a descriptive qualitative method with a library research approach. The data sources consisted of laws and regulations, scientific journals, books, and articles related to domestic violence, divorce, and Bronfenbrenner’s ecological theory. Data were collected through documentation techniques and analyzed descriptively by examining the relationship between microsystem, mesosystem, exosystem, macrosystem, and chronosystem in the occurrence of domestic violence and divorce. The findings indicated that the prevention of divorce due to domestic violence should be carried out comprehensively through healthy family communication, positive social support, emotional control, wise use of social media, the strengthening of religious and moral values, and strict law enforcement. Bronfenbrenner’s ecological approach demonstrated that divorce caused by domestic violence was influenced by the interaction of various environmental systems; therefore, its prevention required the involvement of families, communities, and the government collectively